The Impact of Macroeconomic and Microeconomic Factors on the Profitability of KBMI 3 and 4 Banks - Abadi, Fiter; Limawan, Elaine; Setijaningsih, Herlin Tundjung (Institut Bisnis dan Informatika Kesatuan, 2025)
The banking sector in Indonesia plays a vital role in economic development, particularly through large commercial banks categorized as KBMI 3 and 4, which dominate the financial system. This study aims to examine the influence of macroeconomic factors, namely Gross Domestic Product growth and inflation, and microeconomic factors, specifically bank liquidity and Capital Adequacy Ratio, on the profitability of these banks, measured by Return on Assets, from 2015 to 2023. Using a quantitative approach, the research employs panel data regression to analyze financial reports from major banks and macroeconomic data from official statistical sources. The findings indicate that Gross Domestic Product growth, inflation, and bank liquidity positively and significantly affect Return on Assets, suggesting that economic expansion, stable inflation, and effective liquidity management enhance bank profitability. However, Capital Adequacy Ratio shows no significant impact, indicating that high capital reserves may limit profit-generating opportunities. The study concludes that economic conditions and liquidity are critical drivers of bank performance, while excessive capital requirements may hinder profitability. These insights offer valuable guidance for bank managers to optimize lending strategies and for policymakers to balance regulatory requirements with financial performance goals.